2020
DOI: 10.1111/aogs.14030
|View full text |Cite
|
Sign up to set email alerts
|

Exploring women’s attitudes, knowledge, and intentions to use oocyte freezing for non‐medical reasons: A systematic review

Abstract: Introduction Women are postponing childbearing and preventing age‐related fertility decline with oocyte freezing for non‐medical reasons (OFNMR). The objective of this systematic evaluation was to gain an understanding of women's attitudes and knowledge of, and intentions to use OFNMR among users of OFNMR and the general public. Material and methods A systematic search of MEDLINE, EMBASE, and PyschINFO databases was undertaken, for studies that examined the psychosocial attitudes among women toward OFNMR. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 53 publications
(177 reference statements)
2
31
1
Order By: Relevance
“…A latest systematic review of 17 psychosocial studies found that over 70% of women were single at the time of POC [21]. In our study, only 7% of respondents were in a committed relationship and 71% were ≥ 35 years old when undergoing their first POC cycle.…”
Section: Option-related Changecontrasting
confidence: 49%
See 1 more Smart Citation
“…A latest systematic review of 17 psychosocial studies found that over 70% of women were single at the time of POC [21]. In our study, only 7% of respondents were in a committed relationship and 71% were ≥ 35 years old when undergoing their first POC cycle.…”
Section: Option-related Changecontrasting
confidence: 49%
“…To date, most POC research on women who had undertaken the procedure focuses primarily on evaluating their characteristics, life circumstances, intentions, experience and future utilization plans [17][18][19][20][21]. The influential role of decision regret has only been explored briefly in a few qualitative [23,24] and quantitative [18,24,25] studies, and more in-depth in a US-based single-site follow-up survey study [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hammarberg et al analyzed the reasons for the low usage rate of frozen oocytes, and the most common were found to be single-parent issues, the preference to conceive naturally, and not wanting to use a sperm donor [58], as well as insufficient knowledge and interest of women in the procedure at the optimal age range to perform FP (28-35 years).…”
Section: The Usage Rate Of Frozen Oocytesmentioning
confidence: 99%
“…This was supported by a large randomized clinical trial on oocyte donation that revealed that vitrified oocyte quality was not inferior to fresh oocytes in terms of pregnancy outcomes [21]. Later, oocyte cryopreservation has become a fascinating alternative option for women who attempt in vitro fertilization (IVF) or fertility preservation programs [22]. Benefits of oocyte cryopreservation include increased flexibility to preserve (1) excess oocytes eventually present in each subsequent IVF cycle; (2) fertility in women who are at risk of infertility caused by chemotherapy/radiotherapy/premature ovarian insufficiency (POI) or who prefer to postpone childbearing and prevent age-related fertility decline (>36 years old) [20,22].…”
Section: General Aspects Of Oocyte Cryopreservationmentioning
confidence: 99%
“…Later, oocyte cryopreservation has become a fascinating alternative option for women who attempt in vitro fertilization (IVF) or fertility preservation programs [22]. Benefits of oocyte cryopreservation include increased flexibility to preserve (1) excess oocytes eventually present in each subsequent IVF cycle; (2) fertility in women who are at risk of infertility caused by chemotherapy/radiotherapy/premature ovarian insufficiency (POI) or who prefer to postpone childbearing and prevent age-related fertility decline (>36 years old) [20,22]. Additionally, oocyte cryopreservation technology could facilitate some advantages in routine IVF programs, such as (1) reducing the number of controlled ovarian stimulation cycles in infertile patients; (2) delaying fresh embryo transfer programs aimed at preventing ovarian hyperstimulation syndrome (OHSS) or to optimize artificial endometrial preparation (AEP) and (3) offering options for infertile couples with religious objections to embryo cryopreservation [5,23].…”
Section: General Aspects Of Oocyte Cryopreservationmentioning
confidence: 99%